Medical-Legal Interfaces in Crime Investigation: A Review of Forensic Medicine Applications in Criminal Cases - Jali, Mohammed Mahdi Ali; Alhareth, Dhafer Yahya; Alwily, Khalid Mujahed Ahmed; Wargash, Mohammed Ahmad Al; Hotelah, Mohammed Musfer Mana Al; Alrabie, Rasman Mufleh; Alghamdi, Waleed Ali A; Alshahrani, Hassan Yahya Mofareh (Journal of Posthumanism, 2024)
Forensic medicine plays an essential role in the modern criminal justice system by providing objective scientific evidence that supports crime investigation, reconstruction, and adjudication processes. This review examines the multifaceted medical-legal interfaces that shape the use of forensic medical sciences in criminal cases, highlighting how forensic pathology, toxicology, DNA profiling, sexual assault forensics, and injury evaluation contribute to identifying victims, determining cause and manner of death, interpreting trauma patterns, and linking suspects to crime scenes. Drawing on recent literature published between 2016 and 2025, the article explores significant developments in medico-legal documentation, including chain-of-custody procedures, injury classification frameworks, and digital innovations that enhance the accuracy and reliability of forensic reporting. Special attention is given to the role of forensic experts in court, where medical evidence must be translated into clear, unbiased, and legally admissible testimony. The review also discusses emerging technologies—such as virtual autopsy, AI-assisted image analysis, and rapid toxicology screening—that are transforming forensic investigations. Finally, the article identifies ongoing challenges, including variability in standards, limited resources, and ethical issues, and proposes recommendations to strengthen the integration of forensic medicine within global criminal justice systems